Prospective Associations between Popularity, Victimization, and Aggression in Early Adolescence - Malamut, Sarah T. (J Youth Adolesc, 2020)
Recent research has highlighted an understudied phenomenon in the peer victimization literature thus far: the overlap between high status (i.e., popularity) and victimization. However, the research on this phenomenon has primarily been cross-sectional. The current investigation uses a longitudinal design to address two questions related to high-status victims. First, the present study examined prospective associations between popularity and two forms of indirect victimization (reputational victimization and exclusion). Second, this study examined elevated aggression as a consequence of high-status youth’s victimization (using self- and peer- reports of victimization). Participants were 370 adolescents (M(age) = 14.44, range = 14.00–16.00; 56.5% girls) who were followed for 1 year. Both high and low levels of popularity were prospectively associated with reputational victimization. Moreover, popularity moderated the association between self-reported indirect victimization (but not peer-reported indirect victimization) and aggression. The results help build toward a more comprehensive understanding of both victimization and aggression in adolescence. Findings are discussed in terms of implications for a cycle of aggression in youth and the lowered effectiveness of bullying interventions in adolescence.